Accuracy and calibration of capacitance probe in a Rhodic Ferralsol planted with coffee - Silva, Bruno Montoani; Oliveira, Geraldo César de; Serafim, Milson Evaldo; Silva Júnior, João José da; Colombo, Alberto; Lima, José Maria de (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine the accuracy of the Delta‑T Profile PR2/6 multisensor capacitance probe in the evaluation of soil moisture content using default calibration equations from the manufacturer, to perform the calibration for specific soil sampling locations and depths, and to obtain calibration coefficients for accurate measurements in real time. In January 2010, samples were taken with structure preserved at varying soil depths, at the planting rows or in between the rows. The analyses were done in laboratory using the ML2x Theta probe sensor. After obtaining the outputs from the sensor, water content was determined by the gravimetric method. Samples were taken from a clayed Rhodic Ferralsol. The manufacturer calibration standards (mineral and organic) were not suitable for the evaluated management (sampling location and depths) conditions. Given the impossibility to verify the accuracy obtained by the method indicated by the manufacturer, the use of linear regression adjustments or of the Solver tool was useful in the calibration process. Only two calibration equations are necessary to evaluate the contrasting management situations.